Employee Performance Influenced by Company Culture and Work Discipline, and Motivation as an Intervening Variable in Education Consultants PT MentariBooks Indonesia - Mahmud, Ervan Ali; Fathorrahman, Fathorrahman; Pradiani, Theresia (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Employee performance is an indicator of the quality of human resources (HR) to determine the level of achievement of a department's results related to the organization's vision and to determine the positive and negative effects of operational policies taken and then reported to interested parties for evaluation purposes. The purpose of the research was carried out by educational consultants PT. Mentaribooks aims to see whether there is an influence between company culture and work discipline on employee performance through motivation as an intervening variable. This type of research is quantitative research. The sampling method was a saturated sampling method with the number of respondents being 58 employees of the education consultant section of PT Mentaribooks Indonesia. The data processing method uses multiple linear regression, t test and Sobel test. The research results show that there is a significant influence between company culture and work discipline on performance. Motivation also has a significant influence on performance. The results of the Sobel test also show that motivation also mediates the influence of company culture and work discipline on performance.